PERTANGGUNGJAWABAN HUKUM TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA KEKERASAN SEKSUAL - Surahman; Muhammad Viqran (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
The aim of this research is to determine the factors that cause children to commit criminal acts of sexual violence, as well as to find out and analyze how judges consider in handing down decisions against children as perpetrators of criminal acts of sexual violence in the case of Decision Number 1/Pid.Sus-Anak/2020 /PN Sgt. The method applied in this research is a normative legal research method. This method includes research on library materials which are studied using a statutory approach and a case approach. The legal materials used include primary, secondary and tertiary legal materials. The results of this research are the factors that cause children to commit criminal acts of sexual violence, namely: internal factors originating from within the individual, such as the child's mental, biological and moral conditions, as well as external factors originating from the environment, including socio-cultural, economic and mass media that is easily accessed by children to view adult content. Furthermore, the panel of judges in deciding case No. 1/Pid.Sus-Anak/2020/PN Sgt. It was appropriate to apply Article 76 D of Law Number 35 of 2014 concerning child protection, however the sentences handed down to perpetrators of criminal acts of sexual violence were too light. Children as perpetrators of criminal acts receive legal protection, however, sanctions for these criminal acts should not be too light considering that it is feared that they will not have a deterrent effect on the perpetrators and disrupt order and the general interests of society.